PENGALAMAN PERAWATAN KANKER KOLON STADIUM AKHIR: CASE STUDY - Dwi Retnaningsih; Ericca Ferari; Rahayu Winarti (Jurnal Surya Muda, 2022)
Cancer is a non-communicable disease caused by the increase and growth of cells that grow abnormally in the body. Colon cancer is the third most common malignant cancer in the world. Problems that often arise in cancer patients include physical and non-physical problems. In addition to causing physical problems, cancer also causes psychological, social and economic problems. This study aims to describe the experiences of end-stage colon cancer patients. Qualitative research phenomenological study design, data collection method was in-depth interviews. The research site was at RSI Sultan Agung Semarang, the time of the study was from April to May 2020. The participants in this study were 3 end-stage colon cancer patients, with the criteria of participants suffering from end-stage colon cancer, adults over 18 years old, cooperative and able to communicate and communicate with each other. willing to be a participant. This study found 4 themes, namely when participants were diagnosed with colon cancer (1), the process of grieving colon cancer participants (2), changes in activities and social interactions experienced by participants (3), and participants' spiritual changes during illness (4). Conclusion: Initially, participants were diagnosed with colon cancer, namely signs of symptoms and chronology of participants being diagnosed, the grieving process for colon cancer participants consisted of feelings when diagnosed and considered it as destiny, changes in activities and social interactions experienced by participants, namely there were changes in the activities and relationships of participants' social interactions, and the spiritual changes of participants during illness consist of belief in healing from illness and changes in worship practices.